The Role of Tiktok Social Media in Increasing Student’s Interest In Entrepreneurship - Ginting, Melia Br; Nasution, Muhammad Irwan Padli; Nurbaiti, Nurbaiti (Widya Cipta: Jurnal Sekretari dan Manajemen, 2024)
Business ventures can be carried out by taking advantage of existing online innovation and entertainment, because currently everyone can access and even have a virtual entertainment account that can be used to share data in the form of photos and recordings. TikTok is an online entertainment that is generally popular among millennials for doing business. The reason for this exploration is to find out the extent of the role of social media TikTok in increasing students' interest in entrepreneurship . The population in this study were students at UIN North Sumatra with a total of 100 respondents using a purposive test. The method of collecting information uses surveys, the investigation strategy used is basic straight relapse. The test results show that the dependent variable is TikTok web-based entertainment (X), more or less and at the same time has a significant effect on the independent factor Business Interest (Y), with a value of tcount (8.308) > ttable (1.984). ) and with a Sig level. (0.000) < (0.05), this tends to be reasonable that the TikTok virtual entertainment variable influences interest in business ventures. Regarding the collateral coefficient (R Square), and it means that every 1% increase in TikTok web-based entertainment will increase business interest by 41.3%. Meanwhile, remember The impact of recognizing traditional assumptions shows that the model conditions do not suffer from the adverse effects of multicollinearity problems, do not contain heteroscedasticity and show normal conditions.